(untitled) (Journal for Studies in Humanities and Social Sciences, 2015)
The purpose of this study was to find out Namibian teachers’ understanding of their work circumstances, goals of education for all (EFA) and quality of education. To obtain data on these issues, a structured questionnaire was administered to a proportional representative sample of 1611 primary and secondary school teachers from six regions. Some of the study’s main findings were that several sampled teachers taught under difficult circumstances in which their schools lacked classroom furniture, electricity, water, teaching and learning materials; had problems communicating with parents of their learners; had difficulties managing overcrowded classrooms; were given heavy administrative loads that prevented them from effectively undertaking their teaching duties and that they knew little about the existence of EFA goals. These and other findings are discussed in the paper and developed into insights for enhancing educational practice in Namibia and for identifying issues on which to base further research.